2018
DOI: 10.1111/bre.12320
|View full text |Cite
|
Sign up to set email alerts
|

Can sediment supply variations create sequences? Insights from stratigraphic forward modelling

Abstract: Classic sequence stratigraphy suggests depositional sequences can form due to changes in accommodation and due to changes in sediment supply. Accommodation‐dominated sequences are problematic to define rigorously, but are commonly interpreted from outcrop and subsurface data. In contrast, supply‐dominated sequences are much less commonly identified. We employ numerical stratigraphic forward modelling to compare stratal geometries forced by cyclic changes in relative sea level with stratal geometries forced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Those unconformities are diachronous along the margin, as the sediment supply history driven by the laterally migrating dynamic topography is diachronous. This suggests that variations in sediment supply play a significant role (even a dominant role at delta 5) in controlling the formation of unconformities, supporting the supply-dominated sequences (Zhang et al, 2019). Our results can also provide important insights into identifying those supply-dominated sequences in outcrop and in the subsurface.…”
Section: Geophysical Research Letterssupporting
confidence: 68%
“…Those unconformities are diachronous along the margin, as the sediment supply history driven by the laterally migrating dynamic topography is diachronous. This suggests that variations in sediment supply play a significant role (even a dominant role at delta 5) in controlling the formation of unconformities, supporting the supply-dominated sequences (Zhang et al, 2019). Our results can also provide important insights into identifying those supply-dominated sequences in outcrop and in the subsurface.…”
Section: Geophysical Research Letterssupporting
confidence: 68%
“…The representation of stratigraphic surfaces in linked, syn‐rift deep‐water systems may therefore lie in whether the system is accommodation (in‐situ) or supply (Gilbert‐delta) dominated at a given time or location (Burgess & Hovius, ; Carvajal & Steel, ; Zhang, Burgess, Granjeon, & Steel, ; Zhang, Kim, Olariu, & Steel, ). Zhang, Burgess, et al () and Zhang, Kim, et al () infer that this is principally reliant on shelf width and amplitude of base‐level change from numerical models, where high amplitudes of base‐level variation decrease deep‐water sediment export only in large shelf width, supply‐dominated systems. However, Zhang et al () focus on wide, well‐established shelves.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified sediment supply as the main external driver controlling shelf‐margin growth and its architecture (e.g. Carvajal, Steel, & Petter, ; Schlager, ; Zhang, Burgess, Granjeon, & Steel, ). We argue that the very high Eridanos sediment supply in the earliest Calabrian played an important role in the onset of the outbuilding of upslope‐climbing shelf‐edge scale clinoforms in the study area (Figure ).…”
Section: Discussionmentioning
confidence: 99%